Peran Elit Lokal Partai Golkar dalam Pemenangan Pileg 2014 Kabupaten Langkat - AMOY SRI IRMAYANI SURBAKTI (Politeia: Jurnal Ilmu Politik, 2016)
Golkar Party is the influential party in electoral politics in Indonesia and the region (province and districts). Including Kabupaten Langkat in the Province of Sumatera Utara. This is because the Golkar Party has a lot of famous political elite in society. This studytried to describe about the role of local elite in the winning legislative elections in 2014.The focus discusses how politi-cal elites influence the Golkar party victory in election specifically in Kabupaten Langkat. This study concluded that local elites Golkar party has acted as a complement in the Golkar Party victory in election in Kabupaten Langkat. Besides that some people already believe to Golkar Elite because it is a public figure. The role is very significant because it is associated with the culture, organization, structure and dynamics of politics it self. The research method is used qualitative method. The data collection techniques is interviews. The analysis techniques using qualitative description techniques.Keywords: Local elite, Election, Political parties.